The Profile of quilombola users assisted in the Aurá Family Health Strategy and their perceptions about the health services offered (Research, Society and Development, 2022)
Primary Health Care is seen as the first level of care within the health system, representing the gateway to services, however it is observed that, many times, assistance is uneven, or unsatisfactory in view of the demands of patients, in especially in those of highly vulnerable groups, as is the case with quilombolas. Thus, a descriptive research was carried out with a cross-sectional design and quantitative approach, aiming to analyze the profile of this population, as well as to know their perceptions about the services offered. The main results point to a majority female audience, with an age group of around 49 years. In addition, there was a deficiency with regard to comprehensive care for this population, due to gaps in reception, referral in the health network, waiting time and resolution. It is hoped that this study can support future research and encourage the participation of this public in health services, as well as professionals and managers to offer equitable and comprehensive health to these individuals.